Enhanced high temperature thermoelectric properties of Bi-doped c-axis oriented Ca3Co4O9 thin films by pulsed laser deposition - Sun, T. (2014)
Ca3−xBixCo4O9 (x=0–0.4) thin films were deposited on single-crystal sapphire (0001) substrates by pulsed laser deposition. Structural characterizations indicated that these thin films exhibited perfect c-axis orientation and were well crystallized. Surface chemical states analysis confirmed Bi-substitution for Ca in the thin films with x<0.4. For the thin film with x=0.4, excessive Bi were found isolated within the film. Due to their perfect orientation, in-plane electrical properties of these thin films measured from 300 to 740 K were found to be comparable to those of the single crystals. Furthermore, Bi-substitution was noted for the reduced electrical resistivity and enhanced Seebeck coefficient. The above superior properties resulted in a high power factor of 0.81 mW m−1 K−2 at 740 K for thin film Ca2.7Bi0.3Co4O9, which was about 29% improvement as compared to that of pure Ca3Co4O9 thin film. The results suggested that Bi-doped Ca3Co4O9 thin films could be a promising candidate for thermoelectric applications at elevated temperatures.